2020
DOI: 10.1111/brv.12580
|View full text |Cite
|
Sign up to set email alerts
|

Identifying mechanisms of genetic differentiation among populations in vagile species: historical factors dominate genetic differentiation in seabirds

Abstract: Elucidating the factors underlying the origin and maintenance of genetic variation among populations is crucial for our understanding of their ecology and evolution, and also to help identify conservation priorities. While intrinsic movement has been hypothesized as the major determinant of population genetic structuring in abundant vagile species, growing evidence indicates that vagility does not always predict genetic differentiation. However, identifying the determinants of genetic structuring can be challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 317 publications
0
38
0
Order By: Relevance
“…Such potential geographical separation during the winter season might limit the likelihood of immatures intermixing between the Isle of May and other colonies. Similarly, distinct overwintering distributions have been found to lead to increased genetic diversification in other philopatric seabird species 14,40,43 , such as the thick-billed murre (Uria lomvia) 20 and black-browed albatross (Thalassarche melanophris) 44 . The presence of a Canadian cluster can also be largely explained by their winter distribution around Newfoundland 42,45 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such potential geographical separation during the winter season might limit the likelihood of immatures intermixing between the Isle of May and other colonies. Similarly, distinct overwintering distributions have been found to lead to increased genetic diversification in other philopatric seabird species 14,40,43 , such as the thick-billed murre (Uria lomvia) 20 and black-browed albatross (Thalassarche melanophris) 44 . The presence of a Canadian cluster can also be largely explained by their winter distribution around Newfoundland 42,45 .…”
Section: Discussionmentioning
confidence: 99%
“…The mitogenomic variation suggests that puffins experienced a recent population expansion, possibly out of a refugium after the Last Glacial Maximum. Indeed, it has been shown that mitogenomic variation in seabirds is dominated by historical factors rather than representing contemporary gene flow 40 , and a lack of mitogenomic population structure has been observed in many marine birds with high philopatry e.g. 46,53,54 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms of speciation in seabirds are poorly understood (Friesen 2015). Recently, long-term barriers and population persistence have been proposed as mechanisms for genetic structuring and speciation (Lombal et al 2020), although the high philopatry of seabirds alone could lead to reproductive isolation (Friesen 2015). In addition, allochrony, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Migration can be variously defined, but is often understood as predictable seasonal movement of individuals between locations, and it is widely but heterogeneously distributed across animals (Dingle and Drake 2007). Although migration does not necessitate spatial shifts in reproduction (i.e., dispersal), a positive association is assumed (Lombal et al 2020). As with other dispersal-related traits, migration presents an interesting conundrum with respect to predicting its impact on diversification (McDowall, 1988(McDowall, , 2001Winker 2000;Corush 2019).…”
mentioning
confidence: 99%